Design and manufacture of four wheel tractor for medium size work rice farming - Iwan Harianton; Agus Surjana Saefudin; Muhammad Ali Suparman (Institute of Advanced Engineering and Science, 2023)
Indonesia is located at the equator occupy areas north and south of its bearing atmosphere where about 270 million people live the land of very rich soil and are also rich in mineral sediment demanded heavily for today's technology including nickel, bauxite, lithium, and aurum with its close articles such as thin and uranium. So numerous heavy mining equipment works around the clock. Unfortunately, the other potential products of the rich soil were somehow neglected as the nation left such activities to its traditional practice by utilizing man and animal to cultivate the plantation, so that the productivity of the land from the surface is very minimal such that the average productivity of the soil only reach 27% compared to its champion in the developed countries per acre per year. The study on such low soil productivity is caused by two main problems, such that the lack of massive soil processing technology and low attraction for the worker to pursue their career in farming as more money is offered by the transportation sector being an online transport business. This article is a series published on the tractor research initiative that aims to provide a functional medium tractor powered by a 30 HP engine that can do the basic work of a tractor including lifting soil on the surface so that oxygen will fill up the soil and the mineral can reach the root of the plant life on it and kill the unfavorable weeds in the process. The article will discuss all functional elements of the tractor and necessary specifications from design, manufacturing, and final assembly. Further publications will involve optimal design and construction to head for the final products of its commercial endeavor.